Dangerous Waters: The Economic Toll of Piracy on Maritime Shipping - Renato Molina; Juan Carlos Villase\~nor-Derbez; Gavin McDonald; Grant McDermott (Center for Economic Studies and ifo Institute (CESifo), 2024)
Maritime transport has been historically susceptible to piracy. While broad assessments suggest the impact of modern piracy causes large economic losses, the literature lacks quantification of the magnitude of the costs and the behavioral responses that underpin them. Here, we combine theory and a unique geospatial dataset combining more than 25 million shipping voyages and thousands of pirate encounters across the globe to find that pirate encounters lead to significant and costly avoidance measures. Shippers modify their path along a route to avoid locations with known pirate encounters. This increases voyage distance and duration, which lead to significant increases in fuel and labor costs estimated to be over US1.5 billion/year. Additionally, emission of CO2, NOx, and SOx due to increased fuel consumption results in environmental damages valued at US5.1 billion per year. Together, our results provide the first global estimates linking the presence of pirates to individual behaviour and aggregate transportation cost, as well as its environmental impact, with major implications for the shipping industry and maritime security at a global scale.
Keywords: Q50; F50; R40; 330; piracy; shipping; avoidance